blistered: a gene required for vein/intervein formation in wings of Drosophila. - Fristrom, D.K.; Gotwals, P.; Eaton, S.; Kornberg, T.B.; Sturtevant, M.A.; Bier, E.; Fristrom, J.W. (Development, 1994)
We have characterized the blistered (bs) locus phenotypically, genetically and developmentally using a set of new bs alleles. Mutant defects range from wings with ectopic veins and intervein blisters to completely ballooned wings where the distinction between vein and intervein is lost. Mosaic analyses show that severe bs alleles behave largely autonomously; homozygous patches having vein-like properties. Developmental analyses were undertaken using light and electron microscopy of wild-type and bs wings as well as confocal microscopy of phalloidin- and laminin-stained preparations. bs defects were first seen early in the prepupal period with the failure of apposition of dorsal and ventral wing epithelia. Correspondingly, during definitive vein/intervein differentiation in the pupal period (18-36 hours after puparium formation), the extent of dorsal/ventral reapposition is reduced in bs wings. Regions of the wing that fail to become apposed differentiate properties of vein cells; i.e. become constricted apically and acquire a laminin-containing matrix basally. To further understand bs function, we examined genetic interactions between various bs alleles and mutants of two genes whose products have known functions in wing development. (i) rhomboid, a component of the EGF-R signalling pathway, is expressed in vein cells and is required for specification of vein cell fate. rhove mutations (lacking rhomboid in wings) suppress the excess vein formation and associated with bs. Conversely, rho expression in prepupal and pupal bs wings is expanded in the regions of increased vein formation. (ii) The integrin genes, inflated and myospheroid, are expressed in intervein cells and are required for adhesion between the dorsal and ventral wing surfaces. Loss of integrin function results in intervein blisters. Integrin mutants interact with bs mutants to increase the frequency of intervein blisters but do not typically enhance vein defects. Both developmental and genetic analyses suggest that the bs product is required during metamorphosis for the initiation of intervein development and the concomitant inhibition of vein development.